STRUCTURE OF THE FUNDAMENTAL SOLUTION OF CAUCHY PROBLEM FOR KOLMOGOROV SYSTEMS OF SECOND-ORDER - I.V. Burtnyak; H.P. Malytska (Vasyl Stefanyk Precarpathian National University, 2015)
We study a structure of the fundamental solution of the Cauchy problem for a class of ultra parabolic equations with a finite number of groups of variables with degenerated parabolicity.